Innovative organizations - (:unkn) unknown (Wydawnictwo Politechnika Łódzka, 2008)
In the modern world, a new type of society is being created. A society based on knowledge and information, aimed at innovation. An organisation wanting to develop should show a proinnovative character, i.e. the ability to undertake and implement innovative activities. The presented work is a collection of papers analysing the discipline of innovation in organisations from different perspectives. Each of the chapters is connected with the theory and , methodology of innovativeness and its application. The authors analyse approach innovativeness from different angles which makes the whole work interesting. The work is essential for the development of management due to the multiplanar analyses. It encompasses the following topics: • Innovativeness as the base of organisational success, • Creating and commercialising product innovations, • Innovations in Internet communication, • Banking innovations, • Intellectual property protection in the innovation process. Competition, globalisation and the ability to invest in knowledge are processes which changed management systems in the modem economy, introducing elements of innovation into each enterprise more than ever. One should estimate that innovation and innovativeness are the most important tasks facing enterprises, regions and States in the 21st century. The ability to create and implement innovations became an important challenge of managing organisations. The work is mainly aimed for students but should also interest managers who wish to apply innovations in their organisations. For those reasons, the work analyses the mutual relationship between innovation and economic processes in macro (the whole economy) and micro (the enterprise) scales and the conditions stimulating and influencing those processes. It is an attempt to analyse the chosen aspects of theory and methodology of innovations with a particular emphasis on the conditions and needs of the economy. One may hope that this work will supplement, to a certain level, the theory in the discipline of innovation and management practice of present and future managers.

We współczesnym świecie kształtuje się nowy typ społeczeństwa, opartego na wiedzy i informacji, ukierunkowanego na innowacje. Organizacja chcąc osiągnąć rozwój powinna wykazywać proinnowacyjne nastawienie czyli zdolność do podejmowania i wdrażania przedsięwzięć innowacyjnych. Prezentowana monografia jest zbiorem analizującym problematykę innowacyjności organizacji w różnych aspektach i przekrojach. Zasadniczy kierunek poszczególnych rozdziałów jest związany zarówno z teorią i metodologią innowacyjności, jak i jej możliwościami aplikacyjnymi. Autorzy analizują problematyki innowacji w wielu aspektach tematycznych, co czyni interesującym prezentowane opracowanie. Opracowanie jest istotne dla rozwoju dyscypliny zarządzania poprzez wielopłaszczyznowość podjętych, przez Autorów, rozważań. Obejmuje swoją analizą takie zagadnienia jak: • innowacyjność jako podstawę sukcesu organizacji, • kreowanie i komercjalizację innowacji produktowych, • innowacje w internetowych modelach komunikacji, • innowacje bankowe, • rolę ochrony własności przemysłowej w procesie innowacyjnym. Konkurencja, globalizacja, zdolność inwestowania w wiedzę to procesy, które we współczesnej gospodarce zmieniły systemy zarządzania wprowadzając, do każdej organizacji w znacznie większym zakresie niż dotychczas, elementy innowacji. Należy przypuszczać, że innowacje i innowacyjność są najtrudniejszym z zadań stojących w XXI wieku przed przedsiębiorstwem, regionem i państwem. Zdolność do kreowania i wdrażania innowacji staje się zasadniczym wyzwaniem zarządzania organizacją. Książka ta jest przeznaczona dla studentów, ale powinna również zainteresować menedżerów, którzy pragną stosować innowacje i innowacyjność w swoich organizacjach. Z tego tez względu poddano analizie wzajemne zależności występujące między procesami innowacyjnymi i procesami gospodarczymi w skali makro (całej gospodarki) i mikro (przedsiębiorstwa) a uwarunkowaniami stymulującymi i ograniczającymi wymienione procesy. Praca stanowi próbę analizy wybranych zagadnień teorii i metodologii innowacji ze szczególnym uwzględnieniem warunków i potrzeb praktyki gospodarczej. Można mieć nadzieję, że tak uprofilowane opracowanie przyczyni się, w pewnym zakresie zarówno do uzupełnienia teorii w zakresie innowacji, jak i praktyki działań innowacyjnych obecnych i przyszłych menedżerów polskiej gospodarki.
Red. nauk. Wydz. : Lewandowski, Jerzy
Keywords: innowacje - zarządzanie; przedsiębiorstwo - innowacje; przedsiębiorstwo - zarządzanie; banki - innowacje; innowacyjność organizacji; innovation - management; enterprise - innovation; enterprise - management; banks - innovations; organization`s innovation